Exploração visual interativa de dados coletados pelo sistema integrado de monitoramento ambiental - SIMA - Do Carmo, Alisson Fernando Coelho [UNESP]; Shimabukuro, Milton Hirokazu [UNESP]; De Alcântara, Enner Herenio [UNESP] (My University, 2013)
Researches on environmental phenomena behavior have been benefited from sensor technological advances. Periodic collecting produces long time series, with large data sets composed by a great number of variables. Interactive visual exploration and analysis techniques can be applied to support such data sets processing in order to facilitate the identification of erros and trends, as well as, the detection of patterns. In this context, this paper presents an approach using visual representations for data, associated with interaction techniques, to support the process of identification and understanding the data structures and possible failures in data collected and stored by Integrated System for Environmental Monitoring.
Interactive visual exploration of data collected by the Integrated System for Environmental Monitoring (SIMA)